Layout and Design Considerations for a Wholesale Container Nursery - Christine E. Russo; Thomas H. Yeager; Dewayne L. Ingram; Shawn T. Steed (EDIS, 2023)
The purpose of this publication is to provide nursery professionals considering expansions or those aspiring to start a nursery business with a framework for planning and implementing efficient nursery layouts. Written by Christine E. Russo, Thomas H. Yeager, Dewayne L. Ingram, and Shawn T. Steed, and published by the UF/IFAS Department of Environmental Horticulture, revised June 2023.